Study on The Effect of Ammonium Hydroxide on Survival, Growth, Reproduction and Cocoon Hatching of Eisenia fetida - Nadia Zeguerrou; Rachid Adjroudi (Iranian Journal of Health, Safety and Environment, 2022)
In this study, two chronic toxicity tests were conducted to assess, in vitro, the toxicity effect of ammonium hydroxide 'AH' on survival, growth, reproduction and cocoon hatching of Eisenia fetida worm. Adult earthworms and cocoons were exposed to an increasing AH concentration (0, 0.05, 0.1, 0.5, 1 and 5mg.g-1 of soil). Mortality, growth, cocoon production and juveniles' emerging were measured over 56 days to determine LC50, EC50, NOECs and LOECs values. Moreover, the percentage of hatching success and number of juveniles emerging were recorded. For the first test, our results show that AH caused a high mortality rate, decrease of: biomass, cocoon produced and hatchlings emerging trend with increasing of the AH concentration and exposure time. The calculated LC50 after 28-d was 0.85 and 0.83mg.g-1 after 56-d. Otherwise, the obtained EC50 for biomass changes after 28-d and 56-d were 1.64 and 0.82mg.g-1, indeed, the EC50 of juveniles' production was 0.82mg.g-1. The estimated NOEC value was similar for survival, growth and reproduction (0.5mg.g-1). Otherwise, AH has a toxic character on E. fetida cocoon hatchability, the estimated NOEC value of cocoon hatching success was 1mg.g-1.